Insights into Neuroinflammation in Parkinson's Disease: From Biomarkers to Anti-Inflammatory Based Therapies - Rocha, Natália Pessoa (Biomed Res Int, 2015)
Parkinson's disease (PD) is the second most common neurodegenerative disorder worldwide, being characterized by the progressive loss of dopaminergic neurons in the substantia nigra pars compacta. Among several putative factors that may contribute to PD pathogenesis, inflammatory mechanisms may play a pivotal role. The involvement of microglial activation as well as of brain and peripheral immune mediators in PD pathophysiology has been reported by clinical and experimental studies. These inflammatory biomarkers evaluated by imaging techniques and/or by biological sample analysis have become valuable tools for PD diagnosis and prognosis. Regardless of the significant increase in the number of people suffering from PD, there are still no established disease-modifying or neuroprotective therapies for it. There is growing evidence of protective effect of anti-inflammatory drugs on PD development. Herein, we reviewed the current literature regarding the central nervous system and peripheral immune biomarkers in PD and advances in diagnostic and prognostic tools as well as the neuroprotective effects of anti-inflammatory therapies.